Portrait of Damar Tradition in Welcoming the Arrival of Lailatul Qadar Night in the Community of Patipi Island Village - Muhamad Yusuf; M. Syukri Nawir; Afan Garamatan; Suparto Iribaram; Rachmad Surya Muhandy (Institut Agama Islam Negeri (IAIN) Manado, 2023)
The purpose of the study was to explain the implementation of the Damar tradition in the community of Patipi, Fak-Fak Island Regency, West Papua Province. The Damar Tradition welcomes the night of Lailatul Qadar by lighting torches using resin sap. The research method used a qualitative model with a social phenomenological paradigm and a flow model analysis technique. This research produced several findings regarding implementing the Damar tradition as follows. The Damar tradition in Patipi Island developed orally from generation to generation. Islam, as a religion with plenty of followers in Patipi Island, adapts to its culture to form a tradition in enlivening the night of Lailatul Qadar. Damar tradition begins in the last ten days of Ramadhan month, exactly in the odd number of fasting days: the 21st day, the 23rd, the 25th and the 27th day of fasting, respectively. The Damar tradition can unite the community and form of joy to welcome the night of Lailatul Qadar. The absence of fixed and given goods is a moral idea and shows the citizen's generosity. The gift belongs to the mosque management, so they carry out their duties and responsibilities properly. There is reciprocity in the form of prayers read by the mosque management, a form of dependence between the community and the mosque management. The symbols in the tradition have meanings that can be interpreted by the Patipi island community, in the form of incense burned while reading prayers, Raun or a gift holder made of woven coconut leaves, torches, gifts, and cleaning and giving sand to the grave.